Large power factor and anomalous Hall effect and their correlation with observed linear magneto resistance in Co-doped Bi2Se3 3D topological insulator - Singh R.; Shukla K.K.; Kumar A.; Okram G.S.; Singh D.; Ganeshan V.; Lakhani A.; Ghosh A.K.; Chatterjee S. (My University, 2025)
Magnetoresistance (MR), thermo power, magnetization and Hall effect measurements have been performed on Co-doped Bi2Se3 topological insulators. The undoped sample shows that the maximum MR as a destructive interference due to a π-Berry phase leads to a decrease of MR. As the Co is doped, the linearity in MR is increased. The observed MR of Bi2Se3 can be explained with the classical model. The low temperature MR behavior of Co doped samples cannot be explained with the same model, but can be explained with the quantum linear MR model. Magnetization behavior indicates the establishment of ferromagnetic ordering with Co doping. Hall effect data also supports the establishment of ferromagnetic ordering in Co-doped Bi2Se3 samples by showing the anomalous Hall effect. Furthermore, when spectral weight suppression is insignificant, Bi2Se3 behaves as a dilute magnetic semiconductor. Moreover, the maximum power factor is observed when time reversal symmetry (TRS) is maintained. As the TRS is broken the power factor value is decreased, which indicates that with the rise of Dirac cone above the Fermi level the anomalous Hall effect and linearity in MR increase and the power factor decreases. © 2016 IOP Publishing Ltd.